Icelandic vernacular architecture - Przesmycka, Natalia (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
The article presents the historical determinants and contemporary issues related to the cultural heritage of Iceland - vernacular architecture. This architecture is the result of human activity and very specific conditions of raw environment. The settlement of Iceland historically developed in difficult natural conditions, where the real potential (geothermal energy of the earth) are discovered only in recent years. A small amount of building materials and isolation from other centers of civilization caused that the Icelandic construction has been slightly changed over nearly a thousand years.